Pengaruh Pembelajaran Tematik Integratif Terhadap Kemampuan Berpikir Kreatif Siswa - Atang Sutisna; Santi Rahmawati (JURNAL INOVATIF ILMU PENDIDIKAN, 2020)
This study aims to determine the effect of integrative thematic learning on the creative thinking abilities of fourth grade students at MI PUI Cikaso. This type of research is quantitative with a design form using Quasi Experimental Disgn. The study population was all students in class IV MI PUI Cikaso totaling 48 students. The sample is class IV A as a control class with 24 students and class IV B as an experimental class with 24 students. This study uses 5 items pretest and posttest essay test items. Data collection techniques used were normality test, homogeneity test, and hypothesis testing. The results showed that integrative thematic learning with the help of traditional games had an effect on students' creative thinking abilities. This is evidenced by obtaining the results of the hypothesis Sig. (2-tailed) = 0.002 α = 0.05 then H0 is rejected and H1 is accepted, meaning that there is an effect of integrative thematic learning on students' creative thinking abilities.Keywords: Integrative thematic learning, creative thinking. DOI: http://dx.doi.org/10.23960/jiip.v2i2.21820